Phosphate Solubilization Potentials of Acinetobacter Strains and their Relations with Soil Properties - M. Ogut; F. Er; N. Kandemir (Eurasian Chemico-Technological Journal, 2010)
Phosphate solubilizing bacteria can be used as soil or seed inoculum to increase soil phosphorus (P) availability for agricultural purposes. There is also a possibility of using these microorganisms to biotechnologically dissolve phosphate ores for the production of phosphorus fertilizers. Twenty-one soil samples were collected along a highway in Turkey to isolate phosphate solubilizing bacteria. A total of 20 phosphate solubilizers were isolated from the rhizosphere of wheat and maize grown in the pots, which contained the collected soil samples. The isolates were distributed among the genera, Acinetobacter (7), Pseudomonas (7), Enterobacter (2), Enterococcus (1), Escherichia (1), Photorhabdus (1), and Bacillus (1) as determined by the 16S rDNA gene sequence analysis. Since the Acinetobacter species were most effective in Pikovskaya’s agar, which contained tricalcium phosphate for the sole P-source, they were further experimented for the phosphate solubilization in batch cultures. The mean phosphorus dissolved in 5 day incubation ranged between 167 and 1022 ppm P. The initial pH of 7.8 dropped below 4.7 in six isolates with a gluconic acid production in the concentrations ranging between 27.5 and 37.5 mM. Acinetobacter isolates have some potential as an inoculum both for soil and biotechnological Psolubilization.